The effect of reactive oxygen species on cardiomyocyte differentiation of pluripotent stem cells. (1st February 2018) - Wei, Hua; Cong, Xiangfeng
Abstract: The coordination of metabolic shift with genetic circuits is critical to cell specification, but the metabolic mechanisms that drive cardiac development are largely unknown. Reactive oxygen species (ROS) are not only the by-product of mitochondrial metabolism, but play a critical role in signalling cascade of cardiac development as a second messenger. Various levels of ROS appear differential and even oppose effect on selfrenewal and cardiac differentiation of pluripotent stem cells (PSCs) at each stage of differentiation. The intracellular ROS and redox balance are meticulous regulated by several systems of ROS generation and scavenging, among which mitochondria and the NADPH oxidase (NOX) are major sources of intracellular ROS involved in cardiomyocyte differentiation. Some critical signalling modulators are activated or inactivated by oxidation, suggesting ROS can be involved in regulation of cell fate through these downstream targets. In this review, the literatures about major sources of ROS, the effect of ROS level on cardiac differentiation of PSCs, as well as the underlying mechanism of ROS in the control of cardiac fate of PSC are summarised and discussed.